Social Support Management and Academic Stress: Implications for Students' Subjective Well-being - Kamila, Tasya; Ramadhani, Ayunda (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
The high dropout rate suggests that students' well-being is in doubt, especially in relation to their subjective well-being. This study aims to investigate the impact of perceived social support and academic stress on subjective well-being. This research method uses a quantitative approach. The subjects of this study were 83 students of Faculty Pharmacy X University who were selected by simple random sampling technique. The data collection method used was the subjective well-being scale, social support, and academic stress. The data analysis technique used was multiple linear regression.  The results showed that: (1) there is an influence of social support and academic stress on subjective well-being with the value of F count = 9.367 > F table = 3.11 and p value = 0.000 and has an influence contribution (R2) of 18.6%; (2) there is no significant influence of social support on subjective well-being with a beta coefficient value (β) = 0. 141, t count = 1.284 < t table = 1.989, and p value 0.202 (p > 0.05); (3) there is a positive and significant effect of academic stress on subjective well-being with a beta coefficient value (β) = 0.353, t count = 3.202 > t table = 1.989, and p value 0.002 (p < 0.05). The conclusion in this study is that there is a significant influence between social support and academic stress on students' subjective well-being.